Analisis Penggunaan Agregat Buntu Barana’ Sebagai Agregat Kasar dengan Penambahan Zat Tambah Betonmix Terhadap Kuat Tekan dan Kuat Tarik Belah Beton - Tangnga, Alfaolan Kala'; Sariman, Syahrul; Lebang, Fauzy (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
Along with the very high demand for concrete, therefore the use of dead-end aggregate as coarse aggregate and with the addition of additives for mixed concrete can be used like concrete in general, The aim of the research is to obtain normal concrete with a compressive strength F'c of 25 Mpa, determine the effect of varying Buntu Barana' aggregates (25%, 50%, 75%, 100%) and with the addition of I-3 Betonmix additives on compressive strength, splitting tensile strength of concrete and determining the relationship between compressive and splitting tensile strength of concrete using Buntu Barana' aggregate with the addition of concrete mix. From the results of the study, it was obtained an analysis of the use of Buntu Barana' aggregate as coarse aggregate with the addition of mixed concrete additives to the compressive strength and split tensile strength of concrete. In this study, the compressive strength with 25% of Buntu Barana' aggregate is 27.46 MPa; 50% yielded a compressive strength of 27.08 MPa; 75% yielded a compressive strength of 26.61 MPa; and 100% produces a compressive strength of 25.95 MPa. In the split tensile strength with 25% dead-end aggregate, it is 3.28 MPa; 50% of 3.21 Mpa; 75% of 3.18 MPa and 100% of 2.59 MPa. the equation of the relationship between the compressive strength and split tensile strength of concrete with a value of R2 = 0.95375 and y = 0.9979 x0.34.